IMPLICATION OF CLAY MODIFIED ELECTRODE ON CYANIDE BIOSENSOR - CATHERINA BIJANG,; ABD.WAHID WAHAB,; MAMING,; AHYAR AHMAD, (International Journal of Pharma and Bio Sciences, 2014)
A novel, inexpensive and simple amperometric biosensor based on immobilization of tyrosinase enzyme onto bentonite and modified bentonite is applied for determination of cyanide. The determination of cyanide was performed via its inhibiting action on the tyrosinase electrode. Measurement was carried out using cathecol as substrate. The enzymatically generated quinoid products were electroreduced at 0.1 V vs Ag/AgCl. An extremely sensitive detection limit (2 x 10-7 M) was obtained for cyanide. Enzyme immobilitation onto an modified bentonite seems to cause an increase in cyanide inhibition because of the greater surface area.